The spirit moves west: Korean missionaries in America - Kim, Rebecca Y. (Oxford University Press, 2014)
'The Spirit Moves West' captures the changing dynamics of missions in world Christianity and examines the phenomena of Korean evangelical Protestant missionaries proselytizing Americans, particularly white Americans, in the United States. It answers why and how Korean missionaries evangelized Americans and formed diverse congregations with them and how their mission efforts evolved over time in the West.